2010
DOI: 10.1007/s00222-010-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

Metric differentiation, monotonicity and maps to L 1

Abstract: Abstract. This is one of a series of papers on Lipschitz maps from metric spaces to L 1 . Here we present the details of results which were announced in [CK06, Section 1.8]: a new approach to the infinitesimal structure of Lipschitz maps into L 1 , and, as a first application, an alternative proof of the main theorem of [CK06], that the Heisenberg group does not admit a bi-Lipschitz embedding in L 1 . The proof uses the metric differentiation theorem of Pauls [Pau01] and the cut metric description in [CK06] to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(112 citation statements)
references
References 28 publications
1
110
1
Order By: Relevance
“…Section 1.8 of [10] describes an alternate proof of of the non-embeddability of the Heisenberg group into L 1 which uses metric differentiation in the sense of [23,32], and a classification of monotone subsets of the Heisenberg group. This is carried out in full detail in [13].…”
Section: Results and Techniquesmentioning
confidence: 99%
“…Section 1.8 of [10] describes an alternate proof of of the non-embeddability of the Heisenberg group into L 1 which uses metric differentiation in the sense of [23,32], and a classification of monotone subsets of the Heisenberg group. This is carried out in full detail in [13].…”
Section: Results and Techniquesmentioning
confidence: 99%
“…The main references for this section are [11,12,14,15]. Then we explain the relation between these and Lipschitz maps to L 1 .…”
Section: Tangent Cones Tangent Spaces and Bi-lipschitz Nonembeddingmentioning
confidence: 99%
“…In these cases, monotone sets are half-spaces that might be empty or, at an interior point (density point), might be the whole space; for the case of R n , see [22,23]; for the case of H, see [27]; see also [12,15]. In these cases, monotone sets are half-spaces that might be empty or, at an interior point (density point), might be the whole space; for the case of R n , see [22,23]; for the case of H, see [27]; see also [12,15].…”
Section: Tangent Cones Tangent Spaces and Bi-lipschitz Nonembeddingmentioning
confidence: 99%
“…an RNP Banach space) (see for instance [CK09]), or when B = L 1 (see for instance [CK10a,CK10b,CKN11,CK13]). In connection with embeddings into RNP-Banach spaces, Cheeger and Kleiner [CK09] showed that if (X, µ) is a PI-space the fibres of T X are spanned by "tangent vectors" to Lipschitz curves.…”
Section: Introductionmentioning
confidence: 99%